Pendidikan Karakter Indigenous Dalam Perspektif Al-Qur’an - Yudianto Achmad (Alim | Journal of Islamic Education, 2020)
This study aims to reveal the formulation of concepts and models for the implementation of indigenous character education in the Al-Qur'an perspective for students in premarital, prenatal, and golden ages. The interpretation method of al-Maudhu'i and a qualitative approach are used in this dissertation, in order to produce descriptive data through observation of the letters and verses of the Qur'an, and the science associated with indigenous character education in the perspective of the Qur'an. The results of this study, among others, revealed; 1). Formulation of concepts and models for the implementation of indigenous character education in the perspective of the Qur'an; 2). Religious indigenous character, love for the homeland, intellectuality from the Prophets (Prophet Adam, Prophet Ibrahim, Prophet Muhammad); 3). Character of religious indigenous, love of homeland, taqwā intellectuality (kindness); 4). Religious indigenous character, homeland love, intellectuality fujūr (evil); 5). Formulation of the "TADZKIROH PLUS" implementation model in premarital, prenatal, and golden ages. The conclusion of this study, among others, is that in the perspective of science and the Qur'an, humans from birth have two types of indigenous characters in pairs and are mutually opposite, namely the character of goodness (taqwâ) and character of ugliness (fujûr). Actualization and development through character education that maximizes the character of goodness (taqwâ) and minimizes the character of badness (fujûr).